Analysis on the Shape and Impact Pressure of the High-Pressure Water Jet during the Hydraulic Flushing Cavity Technique. (18th June 2021) - Lu, Shouqing; Wang, Chengfeng; Wang, Wei; Li, Mingjie; Zhang, Dongti
Abstract : A large proportion of minable coal seams in China belong to low-permeability soft coal seams. Such coal seams suffer serious coal and gas outburst hazards and endure a high incidence of major disasters in coal mines. The adoption of the high-pressure water jet (HPWJ) hydraulic flushing cavity can effectively promote the gas drainage efficiency and volume and eliminate the hidden danger of gas disasters. Nevertheless, the shape and impact pressure of rotating HPWJ are rarely researched. In this study, on the basis of the numerical simulation, the axial and radial stress distributions of HPWJ and the energy-gathering effect of a conical-cylindrical combined nozzle were analyzed. It is concluded that the submerged condition will accelerate the attenuation of jet velocity and reduce the impact strength of the jet. The jet diffusion angle grows with the increases in the nozzle diameter and water pressure, and 24° is the optimal contraction angle. Finally, the influences of factors such as the rotation speed on the shape and impact pressure of HPWJ were explored, and the results show that the rotation speed should be controlled within 90 r/min. The research findings lay the foundation of the study on the mechanism of coal crushing by HPWJ and provide technical support for the research and development of drilling and flushing integrated equipment.